THE PROBLEM OF OIL SPILL AND ITS LIQUIDATION BY USING OF ABSORBENTS - Iakovlieva, A.; Khrypko, S. (Science-based technologies, 2014)
Oil and petroleum products occupy one of the first places in the degree of pollution. ]. As oil spill, it floats on water and prevents sunlight to pass through it. The shiny substance that you see sometimes on top layer of water is nothing but oil which makes it difficult for plants and sea animals to survive. Cleaning up of oil spill is no easy task. Various factors need to be considered before carrying out operations. Some of them being amount of oil spilled, temperature of water, type of beaches and many more.The environmental disasters related to oil spills and petroleum product leading to contamination of soil, water bodies. This article is devoted to the problem of oil spill and solving through the use of biomass for absorption in emergencies, tested the possibility of using fallen leaves the possibility as biomas.